Isolated ellipticals and their globular cluster systems III. NGC 2271, NGC 2865, NGC 3962, NGC 4240, and IC 4889 - Salinas R; Alabi A; Richtler T; Lane RR (EDP SCIENCES S A, 2022)
As tracers of star formation, galaxy assembly, and mass distribution, globular clusters have provided important clues to our understanding of early-type galaxies. But their study has been mostly constrained to galaxy groups and clusters where early-type galaxies dominate, leaving the properties of the globular cluster systems (GCSs) of isolated ellipticals as a mostly uncharted territory. We present Gemini-South/GMOS g' i' observations of five isolated elliptical galaxies: NGC 3962, NGC 2865, IC 4889, NGC 2271, and NGC 4240. Photometry of their GCSs reveals clear color bimodality in three of them, but remains inconclusive for the other two. All the studied GCSs are rather poor with a mean specific frequency S (N) similar to 1.5, independently of the parent galaxy luminosity. Considering information from previous work as well, it is clear that bimodality and especially the presence of a significant, even dominant, population of blue clusters occurs at even the most isolated systems, which casts doubts on a possible accreted origin of metal-poor clusters, as suggested by some models. Additionally, we discuss the possible existence of ultra-compact dwarfs around the isolated elliptical NGC 3962.